2020
DOI: 10.21608/pssjn.2020.94023
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Management Strategies Utilized by Nurse Managers and its Relationship to Vertical Dyad Linkage with Nurses

Abstract: Background: Conflict management skill is an essential skill for an effective nurse leader.As inappropriate use of conflict resolution skills leads to degeneration of communication and poor working relationships particularly between nurse leader and their staff nurses.Aim: the current study aimed to determine the relationship between conflict management strategies used by head nurses, and the quality of vertical dyad linkage at Port Said hospitals. Subjects and Methods: A descriptive correlational design was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…45 Nurses in the US commonly use this type of conflict resolution to avoid disagreements and/or prevent serious conflict during confrontation. 46 In Egypt, nurses use the collaborating 32 and accommodating 20 styles the most and the competing style the least. 20 In addition, ElDashan and Keshk 47 confirmed that among Egyptian nurse managers and staff nurses, avoiding was the most preferred, whereas competing was the least preferred CMS, thereby contradicting our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…45 Nurses in the US commonly use this type of conflict resolution to avoid disagreements and/or prevent serious conflict during confrontation. 46 In Egypt, nurses use the collaborating 32 and accommodating 20 styles the most and the competing style the least. 20 In addition, ElDashan and Keshk 47 confirmed that among Egyptian nurse managers and staff nurses, avoiding was the most preferred, whereas competing was the least preferred CMS, thereby contradicting our findings.…”
Section: Discussionmentioning
confidence: 99%
“…46 In Egypt, nurses use the collaborating 32 and accommodating 20 styles the most and the competing style the least. 20 In addition, ElDashan and Keshk 47 confirmed that among Egyptian nurse managers and staff nurses, avoiding was the most preferred, whereas competing was the least preferred CMS, thereby contradicting our findings. In Jordan, the preferred CMS is integrating, whereas the avoiding and dominating styles are the least preferred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in the workplace conditionsin terms of organizational structure and accreditation bodies of control,and the nature of humans in perceiving stressors in di cult situations may explain the variation. Egyptian nurses havestrong relationshipsculturally with colleagues and leaders which makes them accessible and available all the time (Ibrahim et al, 2020).The lower inclusive leadership in Saudi Arabia than the other countries can be justi ed by the extreme shortage of Saudia nurses, and the country relying on nurses from many countries and different cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%